The Asymmetric Impact of Economic Policy Uncertainty on the Demand for Money in the GCC Countries - Elroukh, Ahmed W. (International Journal of Economics and Financial Issues, 2024)
Heightened uncertainty in global economic policy has sparked a renewed interest in studying people’s demand for money, particularly to explore whether this demand exhibits asymmetry. In this study, we utilize a nonlinear ARDL approach to investigate the asymmetric effects of global economic policy uncertainty on money demand in each GCC country. Understanding the impact of global economic policy uncertainty on money demand in GCC countries is essential for crafting effective monetary policies, especially given that these countries maintain a pegged exchange rate to the US dollar, leaving them susceptible to economic slowdowns and global business cycles. The findings show varying sensitivity to changes in economic policy uncertainty across GCC countries, with most countries demonstrating asymmetric responses. Policymakers should consider incorporating a nonlinear ARDL model when analyzing money demand in these nations.